Manufacturing surface technology : surface integrity & functional performance / Brian Griffiths. - Griffiths, Brian (Penton, 2001)
This text marks the recognition of the effect of surface finish obtained in manufacture (surface integrity) on the functional performance of product, in terms of factors such as fatigue, corrosion and strength.